2020
DOI: 10.1016/j.ekir.2019.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Defining Steroid Resistance in Pediatric Nephrotic Syndrome Using Plasma Proteomics

Abstract: Introduction: Nephrotic syndrome (NS) is a characterized by massive proteinuria, edema, hypoalbuminemia, and dyslipidemia. Glucocorticoids (GCs), the primary therapy for >60 years, are ineffective in approximately 50% of adults and approximately 20% of children. Unfortunately, there are no validated biomarkers able to predict steroid-resistant NS (SRNS) or to define the pathways regulating SRNS. Methods: We performed proteomic analyses on paired pediatric NS patient plasma samples obtained both at disease pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 43 publications
2
40
0
Order By: Relevance
“…As has been reported previously, children with SRNS presented at a later age than from those with SSNS (9.5 vs. 5.7 years; P = 0.004). 14 , 17 , 24 As expected, this difference in age was also reflected in significant differences in height and weight between the 2 cohorts ( P < 0.001, see Table 2 ). Moreover, although the SSNS cohort comprised 23% African Americans and 42% Caucasians, the SRNS cohort comprised 43% of each, thus reflecting a significantly greater incidence of SRNS in African American children ( P = 0.001).…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…As has been reported previously, children with SRNS presented at a later age than from those with SSNS (9.5 vs. 5.7 years; P = 0.004). 14 , 17 , 24 As expected, this difference in age was also reflected in significant differences in height and weight between the 2 cohorts ( P < 0.001, see Table 2 ). Moreover, although the SSNS cohort comprised 23% African Americans and 42% Caucasians, the SRNS cohort comprised 43% of each, thus reflecting a significantly greater incidence of SRNS in African American children ( P = 0.001).…”
Section: Resultssupporting
confidence: 74%
“…Although we utilized statistical analyses of the cytokine profiles generated from plasma samples of children with SSNS and SRNS to answer these questions in the present study, we and others have also made other efforts toward the same goal using proteomic, metabolomic, and transcriptomic approaches to identify additional interesting candidates that are either predictive of SRNS or molecularly associated with SRNS. 14 , 15 , 16 , 17 , 18 Over the past few years, serum concentrations of a few cytokines have been associated with relapse in NS. For example, elevated serum levels of IL-8 have been associated with NS relapse, and anti-IL8 antibodies have been shown to neutralize the ability of peripheral blood mononuclear cell culture supernatant to induce albuminuria in rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetics are known to play a role in steroid-responsiveness (Adeyemo et al, 2018;Asharam et al, 2018;Govender et al, 2019;Gribouval et al, 2018Gribouval et al, , 2019. However, while genetic and other mechanisms underlying steroid-responsiveness in this small cohort were not evaluated in the present study, they have been the subject of previously reported biomarker studies (Agrawal et al, 2020;Gooding et al, 2020). Importantly, none of the children in this small cohort were diagnosed with venous thromboembolism, which occurs in ~3% of childhood NS cases (Kerlin et al, 2012a).…”
Section: Hypercoagulopathy Improves In Children With Steroid-sensitmentioning
confidence: 73%
“…This enabled us to use multiple approaches (see Figure 1) to analyze and interpret the dataset, in terms of predicting, mechanistically defining, and differentiating biomarkers in children with SSNS versus SRNS. Notably, this exact same group of patient samples also has undergone plasma proteomics analyses, 44 and we are now initiating studies to identify additional relevant molecular pathways and biomarkers of steroid resistance in NS using approaches to integrate the proteomics and metabolomics datasets.…”
Section: Resultsmentioning
confidence: 99%